2008
DOI: 10.1590/s0101-31222008000200001
|View full text |Cite
|
Sign up to set email alerts
|

Redução na população de plantas sobre a produtividade e a qualidade fisiológica da semente de soja

Abstract: O objetivo deste trabalho foi avaliar os efeitos de reduções na população de plantas sobre a produtividade e a qualidade fisiológica da semente de soja. Duas cultivares de soja (BRSMG 68 Vencedora e M-SOY 8001) foram cultivadas em áreas com e sem o controle de plantas daninhas. As populações estudadas foram: 400.000, 340.000, 280.000, 220.000 e 160.000 pl.ha-1, em um espaçamento entrelinhas de 0,43m. De maneira geral, a presença de plantas daninhas causa decréscimos na produtividade e no tamanho da semente pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 4 publications
4
20
1
11
Order By: Relevance
“…It was the third year of use of the area with agroecological managements, in the beginning of the conversion process from a conventional area to an agroecological, its observed a productivity decrease, which increased with the establishment of the system [36] [37].…”
Section: Resultsmentioning
confidence: 99%
“…It was the third year of use of the area with agroecological managements, in the beginning of the conversion process from a conventional area to an agroecological, its observed a productivity decrease, which increased with the establishment of the system [36] [37].…”
Section: Resultsmentioning
confidence: 99%
“…O uso de populações muito acima da recomendada, além de acarretar aumento nos gastos com sementes, pode levar ao acamamento de plantas e não proporcionar acréscimo na produtividade. Já a adoção de populações abaixo da recomendada favorece o desenvolvimento de plantas daninhas e pode resultar em elevadas perdas no momento da colheita (Vasquez et al, 2008).…”
Section: Introductionunclassified
“…Several studies have been indicating contradictory results of mass of one thousand seeds in relation to plant population. Crusciol et al (2002) and Vazquez et al (2008) did not find variations in the mass of seeds in function of the evaluated plant populations. On the other hand, Tourino et al (2002), evaluating the effect of sowing density and uniformity on productivity and agronomical characteristics of soybeans, found decreases in the mass of seeds.…”
Section: Resultsmentioning
confidence: 72%
“…In their work, Vazquez et al (2008) concluded that variations in plant populations did not cause changes in the germination percentage and accelerated aging in soybeans seeds. On the other hand, Lazarini et al (2001) reported that the sowing density affected seed vigor when evaluated by the accelerated aging and the germination speed index.…”
Section: Resultsmentioning
confidence: 99%